O purismo e a estandarización como factores condicionantes da mudanza linguística : o caso dos plurais dos nomes polisílabos agudos terminados en /-I/ no singular no galego contemporâneo - Ramón Mariño Paz (Linguística, 2008)
In this paper I study how purism and standardization influenced in the modern development of a morphological variable of the Galician language: the plural of the polysyllabical acute nouns finished in /-l/ in their singular form